Effects of MK-801 (dizocilpine) and ketamine on strychnine-induced convulsions in rats: comparison with benzodiazepines and standard anticonvulsants - Kubová, H; Mares, P (Physiological research, 1994)
The effects of two non-competitive NMDA antagonists--MK-801 and ketamine--were studied in a model of generalized seizures elicited by s.c. injection of strychnine (2 or 3 mg/kg) in adult rats. The animals were observed in isolation for 30 min after strychnine administration. Pretreatment with MK-801 (0.5 or 2 mg/kg i.p.) suppressed the tonic, but not the clonic phase of generalized seizures following both doses of strychnine. A similar action of ketamine (20 or 40 mg/kg i.p.) was indicated but it did not attain statistical significance. Strychnine-induced lethality was not changed significantly. A comparison with antiepileptic drugs demonstrated that only phenobarbital (10-80 mg/kg i.p.) was clearly effective against strychnine-induced seizures; carbamazepine (25 or 50 mg/kg i.p.) and partly phenytoin (30 or 60 mg/kg i.p.) were able to suppress the incidence of the tonic phase. Primidone (40 or 80 mg/kg i.p.) as well as the benzodiazpines bretazenil (0.1 or 1 mg/kg i.p.) and midazolam (two lower doses of 0.5 and 1 mg/kg i.p.) were without significant effect. The 2 mg/kg dose of midazolam was partly effective. Only phenobarbital, carbamazepine and the highest dose of midazolam prevented strychnine-induced lethality.
Keywords: modely nemocí na zvířatech; záchvaty; Male; Strychnine; Rats, Wistar; Dizocilpine Maleate; dizocilpinmaleát; mužské pohlaví; potkani Wistar; Seizures; Anticonvulsants; krysa rodu Rattus; Animals; Ketamine; zvířata; Rats; antikonvulziva; Disease Models, Animal; strychnin; ketamin